Genetic Identification of Two Mudskipper Species (Oxudercidae: Periophthalmus) from Kulon Progo, Special Region of Yogyakarta, Indonesia - Diana Febriyanti; Katon Waskito Aji; Dwi Sendi Priyono; Tuty Arisuryanti (Journal of Tropical Biodiversity and Biotechnology, 2023)
Mudskippers are commonly cryptic species, making identification based solely on morphological characteristics challenging. This study used the DNA barcoding method to identify mudskipper species based on the COI mitochondrial gene. The analysis revealed two distinct species, P. kalolo (20 samples) and P. argentilineatus (3 samples) with high GC contents ranging from 42.94-45.2%. The genetic divergence analysis of P. kalolo showed that they divided into two clades, while P. argentilineatus is divided into three clades with two of the clades (C and D)  still conspecific groups, and those two clades with clade E exhibit a genetic distance greater than 3.5%, suggesting the presence of cryptic species. These findings provide valuable insights into the intraspecies genetic diversity of mudskippers in Indonesia, which could have essential implications for conservation efforts and highlight the potential of DNA barcoding as a powerful tool for the identification of cryptic species. Further research combining molecular and morphological identification could lead to a more comprehensive understanding of species identification and help address the challenges posed by cryptic species.